PRAKTIK KONSELING PRANIKAH: SEBAGAI UPAYA GEMBALA SIDANG GEREJA KEMAH INJIL INDONESIA KECAMATAN TEMPUNAK KABUPATEN SINTANG DALAM MENCEGAH TERJADINYA KASUS PERCERAIAN PASANGAN SUAMI ISTRI DALAM RUMAH TANGGA: KONSELING PRANIKAH DI GEREJA KEMAH INJIL INDONESIA KECAMATAN TEMPUNAK KABUPATEN SINTANG - EVENDI, YULIONO (STT INDONESIA MANADO, 2021)
The family is the first marriage institution created by God. God Himself determined a life partner for Adam, the first human. God gave Eve to Adam to be his life partner. God wants what God has joined together man should not separate. In the course of Christian family life, there are many cases of divorce between husband and wife. That is, there is a violation of God's decree. By looking at this phenomenon, every pastor in the local church should carry out premarital counseling before the members of his church carry out the marriage. This is also what pastors in the Indonesian Gospel Tabernacle Church should do Tempunak District,Sintang Regency. In conducting this research, the researcher used a mixed sequential explanatory method. Data collection was carried out through questionnaires, observations and interviews The results showed that there were 54.5% of pastors carrying out premarital counseling, and 63.6% said that there were no divorceases in the church they served.